Subcapsular urinoma following metastasis of testicular embryonal carcinoma - Luu, Doan Tien (Urol Case Rep, 2021)
Urinoma is an uncommon and severe complication that commonly results from ureteral stone formation, causing urinary tract obstruction, urinary tract trauma, or a pelvis mass. Ureter perforation due to malignancy, leading to subcapsular urinoma, is rare. In this article, we aimed to describe a case of secondary subcapsular urinoma in an adult male. The patient was diagnosed with ureter perforation secondary to the invasion of embryonal carcinoma lymph node metastasis.